Shared mobility and public transport – foe or friend? udvidet resumé - Finsveen, Hanne; Pitera, Kelly; Hoen, Fredrik Solvi (Proceedings from the Annual Transport Conference at Aalborg University, 2020)
Shared mobility services have appeared in the city picture, offering a promising solution to sustainable mobility challenges. However, literature shows that they often do not replace car travels, but instead public transit and walking. Through a stated preference survey, information is gathered about how commuters would respond to shared mobility integrated with public transport in their daily travel to work. The objective is to identify if and how it is possible to use shared mobility in connection with public transport to replace personal vehicle use by improving the last mile of the commute, from the bus stop to the office. Results show that every fifth car commuter would leave the car at home and travel by bus if they were guaranteed a free ride with an e-scooter or shuttle from the bus stop to the office. Price was found to be an important attribute while availability of the vehicle was less important. For half of the respondents, infrastructural improvements would not change their stated preferences. E-scooter was the preferred shared vehicle followed by shuttle and then e-bike.